(untitled) (Práxis Educativa, 2020)
This text has as main objective to present a curricular analysis about teacher training by areas of knowledge in the Teaching degree courses in Field Education in the Northeast Region of Brazil. This is a documentary study based on the reading and analysis of curricula and curricular matrices of 11 courses belonging to Federal Universities and Federal Institutes of Education, Science and Technology. As a result, we emphasize, among other aspects, that it is essential to rethink about teacher training by areas of knowledge. Although there are important issues in the curricular organization of the courses, such as, among others, the emphasis given to knowledge and social, cultural, educational content, for example, contributing to a more political teacher education, we understand that the training by areas of knowledge, a central characteristic for teacher training in undergraduate courses, presents itself in the curricula of the courses in a disciplinary perspective. Keywords: Teaching degrees in Field Education. Teacher training by areas of knowledge. Curriculum.